Ionospheric Disturbances Over the Indian Sector During 8 September 2017 Geomagnetic Storm: Plasma Structuring and Propagation - L. Alfonsi; C. Cesaroni; L. Spogli; M. Regi; A. Paul; S. Ray; S. Lepidi; D. Di Mauro; H. Haralambous; C. Oikonomou; P. R. Shreedevi; A. K. Sinha (Space Weather)
Abstract The series of X and M class flares and associated coronal mass ejections that occurred on the first days of September 2017 induced significant perturbations on the low‐latitude ionospheric electrodynamics. On 8 September in the Indian sector, the storm caused a severe modification of the equatorial electrojet (EEJ) with a consequent variation of the ionospheric structuring and dynamics. In our analysis, we propose an original method to isolate and identify EEJ variations from geomagnetic data and we detect the presence of equatorial plasma bubbles (EPB) from L‐band total electron content (TEC) data in order to understand their movement. Our results provide evidence of independent EPBs appearance freshly generated and inherited from a migrating plasma structure. The EPB (or EPBs) occurring in the south of India is/are freshly generated just above the magnetic equator, and is/are likely triggered by the sudden increase of EEJ just before the local sunset, acting as a pre‐reversal enhancement. The EPB appearing in the North‐East Indian region is associated with a migrating structure, resulting in a northward movement with a velocity of about 650 m/s, possibly testifying the passage of a large‐scale traveling ionospheric disturbance. The occurrence of severe post‐sunset scintillations in the northeastern sector suggests a possible cascade process forming small‐scale irregularities from the migrating EPB.